PENGARUH PELATIHAN DAN LINGKUNGAN KERJA TERHADAP LOYALITAS KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada PT Kereta Api Indonesia (Persero) Daerah Operasional 4 Semarang) - Alyani, Niken; Djastuti, Indi (Diponegoro Journal of Management, 2017)
This study aimed to see the impact of training and working environment to the employee loyalty regarding job satisfaction as an intervening variable to the employee of PT Kereta Api Indonesia (Persero) Daerah Operasional 4 Semarang. This study used software smartPLS 2.0.m3 version (Partial Least Square) as the methodology in data analysis. The sample of this study are employee of PT. Kereta Api Indonesia (Persero) Daerah Operasional 4 Semarang with 63 respondents. While data was collected through questioner, surveys, interview and literature review. The result of this study indicates: 1) training has positive and significant impact to the job satisfaction, 2) working environment has positive and significant impact to the job satisfaction, 3) job satisfaction has positive and significant impact to the employee loyalty, 4) training has positive and significant impact to the employee loyalty, 5) working environment has positive and significant impact to the employee loyalty, 6) training has positive and significant impact to the employee loyalty through job satisfaction, 7) working environment has positive and significant impact to the employee loyalty through job satisfaction.